UNDERSTANDING AND IMPROVING PATIENT PORTALS FOR OLDER ADULTS - Dhillon, Jasdeep (My University, 2025)
As technology advances, we see the digitization of many crucial services, including healthcare. Patient portals provide patients with quick access to their personal health information, the ability to perform health management tasks, educational materials, and more. Patient portals are rapidly increasing in adoption, and becoming a core part of the healthcare experience. Although patient portals show promise in improving healthcare outcomes and experiences, these solutions are not equally accessible to all. Older adults face unique barriers to using patient portal including limited digital literacy, physical and cognitive limitations, and issues arising from a lack of consideration of older adults in patient portal design. This thesis examined the state of patient portal use amongst older adults, facilitators and barriers to portal use and adoption, frameworks and strategies to improve the adoption and use of patient portals, and roadmaps for selecting and including these frameworks into patient portal development and implementation. Chapter 2 employed a systematic review to examine the use of patient portals by older adults, the features most frequently accessed by older adults, and the facilitators and barriers to older adults’ use and adoption of patient portals. The systematic review revealed lower use of patient portals amongst older, low socioeconomic status, low education, non-English speaking older adults, amongst other factors. Patient portals were most frequently used to access personal health information, or perform health management tasks such as booking appointments or renewing prescriptions. The barriers and facilitators revealed pathways forward; building trust and value, supporting and engaging portal use, advancing community capacities, and simplifying patient portals. These pathways surrounded by a focus on EDI can serve to make patient portals more accessible for older adults of all walks of life. Chapter 3 employed a multi-modal search of databases and gray literature to provide a list of 11 frameworks, 6 of which can be used to ensure equity is promoted, 3 of which are focused specifically on pathways to improving use and adoption of technologies, and 2 of which are focused on ensuring the protection and control of sensitive data by minority groups. Chapter 4 brings the findings of earlier sections together by exploring actionable pathways to implementing the suggestions made in Chapter 2 and Chapter 3. Chapter 4 lays out roadmaps for incorporating frameworks for the improvement of equity within development and implementation projects and lays out liberatory design as a potential pathway for developers to consider EDI throughout the design process.
EVALUATING AND IMPROVING THE USE, INCLUSIVITY, AND ACCESSIBILITY OF PATIENT PORTALS FOR OLDER ADULTS
Keywords: Patient Portal; Electronic Health; Older Adult; Accessibility; Diversity; Inclusion; Equity; EDI; Implementation; Development; Design; eHealth; MyChart; Personal Health Record; EHR; EMR; Electronic Health Record; Electronic Medical Record; PHR; PHI; Telehealth; Digital Literacy